O dualismo pulsional em Freud - Marioto, Sabrina (2017)
The purpose of this paper is to discuss Freud's dualistic drive, arguing that the transition from one dualism to another is not a rupture in his theory, but rather a movement in his thinking. For this, we start from the analysis of the concept of drive, marking its specificity when compared to the animal instinct and showing how the sexual drives and the drives of self-preservation allowed the appearance of two different ways of processing the psychic energy. Next, we deal with the psychic conflict that begins with the process of repression and has as a background duel between sexuality and self-preservation, a subject that interests us, because we will see how the clinic and its impasses end up bringing problems to the first Theory. For this reason, we will deal with the difficulties brought about by paraphrenias and by the concept of narcissism that end up smoothing the first dualism. Finally, we will see how traumatic neurosis and the compulsion to repetition bring new elements to Freud and culminate in the elaboration of a new definition of the drive, which will now also be thought from the dispute between the life drives and the death drive.